Application-based Smart Parking System using CAN Bus - Rahul Muppanagouda Patil; N R Vinay; Pratiba D (Institute of Advanced Engineering and Science, 2018)
We have witnessed a rapid growth in the Internet of Things and its contribution to the growth of Smart cities in recent years. Consistent efforts have been undertaken by the Government of India to elevate the growth of this industry. The increase in population and vehicular densities have led to congested roads, inadequate parking facilities and poor infrastructure has called for a technology-driven solution known com-monly as a Smart Parking System (SPS). The solution proposed in this paper is a client-based parking slot reservation system that is implemented using micro-controllers interfaced with sensors for parking vacancy detection. They are also connected to cloud services in order to produce a complete IoT solution, with each micro-controller acting as a node in a network. Additionally, the CAN protocol is deployed for communication between nodes of this network in case of failure of the nodes in the wireless network. This is a solution de-veloped that caters to users mainly residing in Smart Cities and addresses the issue of network node failure.